Ultimate tensile and compressive strength of concrete containing coir fibers - Labadan, Milon P. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2000)
This paper describes the results of the study to determine the feasibility of coir fibers as reinforcement to concrete, specifically to evaluate the ultimate tensile and compressive strength of concrete containing coir fibers. The average ultimate tensile and compressive strength of plain concrete and concrete containing various amounts and lengths of coir fibers were determined and their strengths compared. Generally, the addition of coir fibers has negative influence on the compressive and tensile strength of concrete, but the addition of fibers converts the sudden and brittle failure of plain concrete in tension into gradual and ductile failure.